Sequencing JIT Mixed-Model Assembly Lines Under Station-Load and Part-Usage Constraints - Drexl, Andreas; Kimms, Alf (Management Science, 2001)
This paper deals with two most important problems, from both practical and theoretical standpoints, arising in sequencing mixed-model assembly lines. Such lines have become core components of modern repetitive manufacturing, and just-in-time (JIT) manufacturing in particular. One problem is to keep the usage rate of all parts fed into the final assembly as constant as possible (the “level-scheduling problem”), while the other is to keep the line's workstation loads as constant as possible (the “car-sequencing problem”). In this paper the combined problem is formulated as a single-integer programming model. The LP-relaxation of this model is solved by column-generation techniques. The results of an experimental evaluation show that the lower bounds are tight.